2001
DOI: 10.1097/00054725-200111000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Crohn's Disease: Analysis According to the Vienna Classification and Clinical Activity

Abstract: The aim of this study was to describe the clinical course of Crohn's disease (CD) in a well-defined, homogeneous groups of patients. A total of 480 patients with CD were followed up from diagnosis up to 20 years. Definitions of patient subgroups were made according to the Vienna Classification. Markov chain analysis was used to estimate the probabilities of remissions and relapses during the disease course. Both age at diagnosis and behavior were associated with different disease locations. Patients with ileal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
58
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(74 citation statements)
references
References 25 publications
12
58
1
3
Order By: Relevance
“…In the historical national cooperative CD study, perianal disease was an independent predictor of unfavourable outcome among 1084 patients [17] . In a Portuguese referral centre cohort testing CD outcome according to Vienna classification and other clinical markers, earlier age at diagnosis, penetrating lesions (including perianal fistulas and abscesses) and ileo-colonic location were associated with unfavourable outcome [18] . In the Olmstedt population-based study, young age was predictive of surgery, irrespective of smoking status [19] .…”
Section: Clinical Predictors Of CD Coursementioning
confidence: 99%
“…In the historical national cooperative CD study, perianal disease was an independent predictor of unfavourable outcome among 1084 patients [17] . In a Portuguese referral centre cohort testing CD outcome according to Vienna classification and other clinical markers, earlier age at diagnosis, penetrating lesions (including perianal fistulas and abscesses) and ileo-colonic location were associated with unfavourable outcome [18] . In the Olmstedt population-based study, young age was predictive of surgery, irrespective of smoking status [19] .…”
Section: Clinical Predictors Of CD Coursementioning
confidence: 99%
“…Santos Dumont, km 5 -Condomínio Parque Encontro das Águas, Lote G31 -42700-000 -Lauro de Freitas, BA, Brazil. E-mail: genoile@uol.com.br et al (14) detected differences in prognosis between subgroups of patients with Crohn's disease classified according to criteria of Vienna. LOUIS et al (9) found changes in the clinical behavior during the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with perianal disease were more likely to have colonic disease (30) whereas patients with internal fistulizing disease were more likely to have ileal or ileocolonic disease and are more likely to require intestinal resection (31).…”
Section: Introductionmentioning
confidence: 99%